Micro-CT evaluation of the removal of root fillings using rotary and reciprocating systems supplemented by XP-Endo Finisher, the Self-Adjusting File, or Er,Cr:YSGG laser - Gülsen Kiraz; Bulem Üreyen Kaya; Mert Ocak; Muhammet Bora Uzuner; Hakan Hamdi Çelik (Restorative Dentistry & Endodontics, 2023)
ObjectivesThis study aimed to compare the effectiveness of a single-file reciprocating system (WaveOne Gold, WOG) and a multi-file rotary system (ProTaper Universal Retreatment, PTUR) in removing canal filling from severely curved canals and to evaluate the possible adjunctive effects of XP-Endo Finisher (XPF), the Self-Adjusting File (SAF), and an erbium, chromium: yttrium, scandium, gallium garnet (Er,Cr:YSGG) laser using micro-computed tomography (μCT).Materials and MethodsSixty-six curved mandibular molars were divided into 2 groups based on the retreatment technique and then into 3 based on the supplementary method. The residual filling volumes and root canals were evaluated with μCT before and after retreatment, and after the supplementary steps. The data were statistically analyzed with the t-test, Mann-Whitney U test, analysis of covariance, and factorial analysis of variance (p < 0.05).ResultsPTUR and WOG showed no significant difference in removing filling materials (p > 0.05). The supplementary techniques were significantly more effective than reciprocating or rotary systems only (p < 0.01). The supplementary steps showed no significant differences in canal filling removal effectiveness (p > 0.05), but XPF showed less dentin reduction than the SAF and Er,Cr:YSGG laser (p < 0.01).ConclusionsThe supplementary methods significantly decreased the volume of residual filling materials. XPF caused minimal changes in root canal volume and might be preferred for retreatment in curved root canals. Supplementary approaches after retreatment procedures may improve root canal cleanliness.